Staphylococcus aureus skin colonization in atopic dermatitis patients - Hasse-Cieślińska, Marta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Introduction: The skin of up to 100% of patients with atopic dermatitis is colonized with Staphylococcus aureus . Of all S. aureus strains isolated from lesional skin, up to 65% have been shown to produce exotoxins. Aim: The aim of this study is to determine S. aureus colonization rate and density on affected and unaffected skin and nasal mucosa in patients with atopic dermatitis, with psoriasis, and in healthy controls. Material and methods: We examined 25 patients with atopic dermatitis selected according to features of Hanifin and Rajka. Two sex- and age- matched groups were selected as controls: 25 patients suffering from psoriasis and 25 healthy individuals. In all of them we examined the prevalence of nasal S. aureus carriage, and staphylococcal colonization on the skin (normal appearing and lesional skin). Using contact plates the density of staphylococcal skin colonization was estimated. We examined the prevalence of producers of SEA or SEB among strains of S. aureus isolated from sampled skin. Results and conclusions: In patients with atopic dermatitis the prevalence of nasal S. aureus carriage was 64%. The prevalence of S. aureus skin colonization was 56% on normal appearing skin and 68% on lesional skin. The density of staphylococcal colonization was high especially on lesional skin. Differences between patients with atopic dermatitis and control groups were statistically significant. The prevalence of producers of SEA or SEB among strains isolated from atopic dermatitis patients was 29.4% compared to 16.6% among strains isolated from psoriatic patients.